2021
DOI: 10.1111/sms.14000
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs after a 24‐h ultramarathon run in relation to muscle damage markers in elite athletes

Abstract: Ultra‐endurance sports are growing in popularity but can be associated with adverse health effects, such as exercise‐induced muscle damage (EIMD), which can lead to exertional rhabdomyolysis. Circulating microRNAs (miRNAs) may be useful to approach the degree of EIMD. We aimed to (1) investigate the relevance of circulating miRNAs as biomarkers of muscle damage and (2) examine the acute response of skeletal/cardiac muscle and kidney biomarkers to a 24‐h run in elite athletes. Eleven elite athletes participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
11
2
2
Order By: Relevance
“…The results of the current study are similar to previous studies in which Mb returned to baseline 24 h following intense exercise in trained athletes [ 83 , 84 ]. This is significant, as the magnitude of Mb response is associated with the mode, intensity, and duration of the exercise performed [ 48 , 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are similar to previous studies in which Mb returned to baseline 24 h following intense exercise in trained athletes [ 83 , 84 ]. This is significant, as the magnitude of Mb response is associated with the mode, intensity, and duration of the exercise performed [ 48 , 85 , 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a systematic review of the literature reports conflicting results on the ability of statins to impair performance during exercise [158]. The increase in circulating levels of specific microRNAs (myomiRs) has recently been indicated as a potential biomarker of muscle quality [159]. It has been described that an increase in the levels of some myomiRs is related to intense exertion (miR-1, miR-133a, miR-206), and one in particular (miR-499-5p) seems to increase only in athletes on therapy with statins [160].…”
Section: Physical Exercisementioning
confidence: 99%
“…In addition, it was revealed that miR-133b played important roles in various diseases. MiR-133b may play a crucial role in suppression genes associated with humans and mice cleft lip (Yoshioka et al, 2021), and act as biomarker in cardiovascular disease (Chang et al, 2021), muscle atrophy (Malacarne et al, 2021), muscle damage (Chalchat et al, 2021). Moreover, lots of reports demonstrated that miR-133b harbored the ability in cardiomyocyte protection in dealing with hypoxia injury (Pan et al, 2018;Zhou et al, 2019) and morphine preconditioning (He et al, 2016).…”
Section: Discussionmentioning
confidence: 99%